Modernidade e sociabilidade: do "comércio" ao shopping (Belém-PA, 1990-) - SODRÉ, Marcelo Santos (Universidade Federal do Pará, 2012)
This work is fruit of a research that we carry through between the years of 2004 and 2005, in Belém (Pará), that in it took them to understand and to explain as Modernity was developed in shopping Iguatemi Belém, through one of its main institutions: market capitalist, which by means of the socialization (panoptismo), "dictated" the behaviors of the visitants, generating species of practical relationary (sociability) that, "anchored" to the phenomenon of the search for prestige and social status of the positional type, a mechanism of social differentiation it provided that were initiated in the "commerce" (Street João Alfredo) and "it discharged" in shopping Iguatemi Belém, where the decurrent values of the socialization process studied here started to reproduce and to accent the proper process of social distinction between the "classrooms high and average high" and the "classroom low".